2008
DOI: 10.1111/j.1601-5215.2007.00244.x
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of memory compromise in chronic geriatric schizophrenia, frontotemporal dementia and normal geriatric controls

Abstract: RESULTS failed to show distinctions between groups on pattern of memory impairment when using discrepancy comparisons. However, an analysis examining percentage retention scores revealed better maintenance of non-contextual visual information over time in SSD. Findings may suggest deficits in immediate encoding rather than memory decay for some types of memory ability among geriatric SSD. Our failure to document group differences when using discrepancy comparisons may be attributable to relative similarity in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The intermediate cluster (Cluster 2) performed worse than previously reported scores in healthy individuals, implying some impairment was present. For example, in WMS-III logical memory, Cluster 2 (mean raw scores: LNS: 9.23, LM-1: 9.90, LM-2: 9.94) performed significantly worse than a large control group ( N = 330 mean age of 36, LNS: 12.72) from Cosgrove, et al 44 and performed worse even compared to a healthy older control group ( N = 107, mean age = 71, LM-1: 10.77, LM-2: 11.52) from Foley, et al 45 reported average scores of 10.77 and 11.52 for the WMS-III logical memory (1 and 2) subtests in a sample of 107 older controls aged between 55 and 93 (mean age = 70.97). In contrast, our Cluster 2 performed well below these (mean raw scores: LNS: 9.23, LM-1: 9.90, LM-2: 9.94), despite the scores from Foley et al (all p values < 0.05).…”
Section: Discussionmentioning
confidence: 94%
“…The intermediate cluster (Cluster 2) performed worse than previously reported scores in healthy individuals, implying some impairment was present. For example, in WMS-III logical memory, Cluster 2 (mean raw scores: LNS: 9.23, LM-1: 9.90, LM-2: 9.94) performed significantly worse than a large control group ( N = 330 mean age of 36, LNS: 12.72) from Cosgrove, et al 44 and performed worse even compared to a healthy older control group ( N = 107, mean age = 71, LM-1: 10.77, LM-2: 11.52) from Foley, et al 45 reported average scores of 10.77 and 11.52 for the WMS-III logical memory (1 and 2) subtests in a sample of 107 older controls aged between 55 and 93 (mean age = 70.97). In contrast, our Cluster 2 performed well below these (mean raw scores: LNS: 9.23, LM-1: 9.90, LM-2: 9.94), despite the scores from Foley et al (all p values < 0.05).…”
Section: Discussionmentioning
confidence: 94%
“…On LILACS, none of the nine retrieved met the requirements. Therefore, 42 articles were selected, of which 10 were cohort studies 15,16,17,18,19,20,21,22,23,24 , three were case-control studies 25,26,27 , 12 were case repo rts 28,29,30,31,32,33,34,35,36,37,38,39 and 17 other studies were cross-sectional surveys 6,7,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54 .…”
Section: Resultsmentioning
confidence: 99%
“…The results indicated that the SCZ group had impaired performances on all theory of mind conditions, despite understanding sincere statements. Nonetheless, bvFTD patients had remarkable impairment in identifying sarcasm, and seemed to benefit from verbal tips that indicated the appropriate social context, suggesting that these patients were particularly impaired in detecting discrete nonverbal signs from the scene 54 . In another study, Bediou et al explored facial emotional recognition performance in different clinical conditions, including SCZ and bvFTD.…”
Section: The Very Concept Of Scz Emerged In 1896 Withmentioning
confidence: 99%